CRGD-functionalized nanoparticles for combination therapy of anti-endothelium dependent vessels and anti-vasculogenic mimicry to inhibit the proliferation of ovarian cancer. (August 2019) - Wang, Yifeng; Tong, Lin; Wang, Jianguo; Luo, Jiamao; Tang, Jiao; Zhong, Lijuan; Xiao, Qian; Niu, Wenbo; Li, Jinheng; Zhu, Junqiao; Chen, Huajian; Li, Xin; et al.
Graphical abstract: Abstract: Accumulating evidence has disclosed effective anti-angiogenic strategies should simultaneously inhibit endothelium-dependent vessels (EDV) and tumor cell-mediated vasculogenic mimicry (VM). The αv β3 integrin-targeting peptide cRGD has the ability to inhibit EDV and we have found cRGD can also suppress the formation of VM in ovarian cancer cells. Herein, a cRGD-based combination strategy was developed to suppress the proliferation of tumor cells by anti-EDV and anti-VM. We firstly engineered two cRGD functionalized nanoparticles (cRGD-NPs1 and cRGD-NPs2) by self-assembly using heparin conjugated with cRGD and folate. In vitro experiments demonstrated cRGD-NPs2 exhibited more significant cytotoxicity and higher intracellular uptake ability than cRGD-NPs1. Also, cRGD-NPs2 could efficiently discourage EDV, VM and proliferation in HUVECs and SKOV3 (VM+) cells. In vivo studies showed cRGD-NPs2 could specifically accumulate in ovarian cancer tissues and exerted a superior anti-tumor effect in SKOV3 xenografts. The mechanisms responsible for creating anti-EDV and anti-VM action of cRGD-NPs2 related to combined effects of cRGD, heparin and folate. The results demonstrated cRGD-NPs2 represented a versatile anti-angiogenic medicine via their combined inhibitory effect. Statement of Significance: Accumulating documents indicate tumor cell-mediated vasculogenic mimicry (VM) is positively correlated with poor prognosis, occurrence of distant metastasis and low survival rate in cancer patients, suggesting VM is a potential therapeutic target for cancer treatment. Thus, effective anti-angiogenic strategies should simultaneously inhibit VM as well as endothelium-dependent vessels (EDV). Integrin αv β3 is a crucial inducer involved in the formation of both EDV and VM. In this study, we engineered αv β3 integrin-targeting peptide cRGD functionalized nanoparticles (cRGD-NPs) by self-assembly using heparin conjugated with cRGD and folate. The prepared cRGD-NPs represent a promising anti-angiogenic medicine in that they are able to inhibit endothelial sprouting angiogenesis and tumor cell-mediated VM. This work may provide useful information with which to construct effective anti-angiogenic nanomedicines.